Benefits of Women's Empowerment in Midwifery Services: Scooping Review - Juniarti, Shania; Ramayani, Ramayani; Gunarmi, Gunarmi; Mularsih, Sri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Empowering women in the health sector is an important element of women's human rights and reducing gender inequality towardsacceleration of SDGs achievement targets in the third and fifth